2018
DOI: 10.1542/peds.2018-0502
|View full text |Cite
|
Sign up to set email alerts
|

General Pediatricians and Value-Based Payments

Abstract: Although experience and views vary, just more than half of surveyed pediatricians report receiving some form of VBP. Pediatricians reporting this experience are more likely to feel that these payment models have a positive impact on patient care when compared with pediatricians without this experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Increased coverage of developmental topics may enhance quality measures, (for example, completed developmental screening (Hirai et al, 2018) as well as advance the goals of pediatric care redesign, described as rethinking the process and content of well-child care to better reflect the known distribution of child health needs Schor, 2009;Schor 2004). To the degree that guideline-concordant or high-quality care is tied to reimbursement and revenue (Tieder et al, 2018), studies showing improvements in these factors may also have implications for cost.…”
Section: Discussionmentioning
confidence: 99%
“…Increased coverage of developmental topics may enhance quality measures, (for example, completed developmental screening (Hirai et al, 2018) as well as advance the goals of pediatric care redesign, described as rethinking the process and content of well-child care to better reflect the known distribution of child health needs Schor, 2009;Schor 2004). To the degree that guideline-concordant or high-quality care is tied to reimbursement and revenue (Tieder et al, 2018), studies showing improvements in these factors may also have implications for cost.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Izguttinov et al [27] found that physicians identified education and physician/staff training influenced physician behavior change as new payment models evolve. Existing research also showed that physicians/physician practices with prior performance incentives and public reporting experience were more likely to have a positive attitude toward P4P program compliance and elect to participate in new programs [28] , [5] . This study confirms findings from the existing body of literature demonstrating that physician knowledge of P4P program design and impact on patient outcomes influences physician attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, U. S. health care spending reached $3.65 trillion dollars, and policymakers expect that number to grow to $5.7 trillion dollars by 2026 [1] , [2] . To produce predictable and consistent patient outcomes, pay for performance (P4P) programs encourage behavior change to reduce waste, use technology, coordinate care, or improve adherence to clinical guidelines through financial incentives to influence how physicians practice medicine [3] , [4] , [5] . According to a survey by the American Medical Association, 59.1% of physicians in the U. S. received some revenue from a P4P in 2016 [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, offering a "Feminine Hygiene Fact Sheet" to respondents who completed the questionnaire may have encouraged pediatricians interested in the topic to participate, though the "ADHD Medication Guide" was used to incentivize participation independent of this interest. Also, female pediatricians, who had higher scores on average than male pediatricians, may have been overrepresented, as 78.8% of respondents were female, compared to 66.9% of primary care pediatricians nationally [31]. Moreover, pediatricians' practices were self-reported, and though the questionnaire was anonymous, responses may have been affected by social desirability.…”
Section: Discussionmentioning
confidence: 99%